МЕМЛЕКЕТТІК БАСҚАРУДЫҢ ТИІМДІЛІГІН АРТТЫРУ ФАКТОРЫ РЕТІНДЕ МЕМЛЕКЕТТІК ҚЫЗМЕТ ЖҮЙЕСІНДЕГІ СЫБАЙЛАС ЖЕМҚОРЛЫҚҚА ҚАРСЫ ІС-ҚИМЫЛ (Journal of actual problems of jurisprudence, 2019)
This article examines the comprehensive definitions of corruption given by many scientists and the history of corruption. Besides, the state of corruption in our country and other States is stated. This article discusses various normative legal acts, state programs, international treaties aimed at combating corruption in the legislation of the Republic of Kazakhstan, as well as other normative legal acts aimed at combating corruption and the President’s Address to the people. The ways of corruption eradication and measures for the formation of anti-corruption culture in each sphere of society are presented. In addition, this article reflects the principles and objectives of anti-corruption, the activities of the authorized bodies to combat corruption and anti-corruption restrictions. In addition, the issues of responsibility for corruption crimes and administrative offenses are described. Despite the fact that the country has a lot of articles on this topic, each of them is different methods of research and measures of corruption protection, recommendations for the eradication of corruption in society. Therefore, this article discusses indetail the issues of corruption from the history to the present state.Key words: corruption, offense, law, criminal liability, administrative responsibility, anti-corruptionculture, bribery.